2018
DOI: 10.1021/acs.jpcc.8b07357
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects in Protonation Reactions Catalyzed by Zeolites with Large Void Structures

Abstract: In the present work, we studied the protonation reaction of styrene inside the cavity of acidic H-Y zeolite. Density functional theory calculation using M06-2X functional and analysis of quantum theory of atoms in molecules are used to investigate the confinement effects of zeolite framework on species involved on the reaction. A detailed analysis of the topology of the electron density of interactions among reactants, transition state, and intermediate products with the cavity of H-Y zeolite is performed, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
(105 reference statements)
0
12
0
Order By: Relevance
“…In their investigation of mechanism of olefin elimination in the methanol-to-olefin process over different zeolites, Wang et al 57 found that the actual reaction routes for olefin elimination are strongly related to the pore structure of zeolite catalysts; therefore, the confinement of the zeolite pore has a greater effect on the mechanism. Zalazar et al 58 studied the protonation reaction of styrene inside the cavity of acidic H−Y zeolite and analyzed the topology of the electron density of interactions among reactants, transition state, and intermediate products. They found that the zeolite confinement effect is a crucial factor that may affect the catalytic activity.…”
Section: −O H − T 11mentioning
confidence: 99%
“…In their investigation of mechanism of olefin elimination in the methanol-to-olefin process over different zeolites, Wang et al 57 found that the actual reaction routes for olefin elimination are strongly related to the pore structure of zeolite catalysts; therefore, the confinement of the zeolite pore has a greater effect on the mechanism. Zalazar et al 58 studied the protonation reaction of styrene inside the cavity of acidic H−Y zeolite and analyzed the topology of the electron density of interactions among reactants, transition state, and intermediate products. They found that the zeolite confinement effect is a crucial factor that may affect the catalytic activity.…”
Section: −O H − T 11mentioning
confidence: 99%
“…Mesoporous silicate materials have received widespread attention of late due to their applications as supports for catalysis, in separation techniques, and in the confinement of guest molecules. Siliceous host environments have also generally been important in the realm of heterogeneous catalysis, where protonation reactions with guest molecules can form carbocation intermediates , which can then undergo charge neutralization to give neutral H-adduct free radicals. Such radicals can also be formed by direct H atom transfer/addition reactions to unsaturated bonds in these environments, , a well-known mechanism for hydrogenation reactions in general , and for the hydrogenation of benzene in particular. Though interfacial interactions of this nature are well-known to be important in surface chemistry, , including for H atom reactivity, there are very few direct measurements of H atom reaction rates in heterogeneous systems, thus providing an important motivation for the present study of the analogue reactions of the muonium atom.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalysis has been an important topic in the chemical sciences for many years, ,, in which oxide environments in general , and silicious environments in particular, including mesoporous silica ,,, and zeolites, have often been used as supports for catalytically active species. The acidic properties of such environments , are also important, via proton or H atom transfer reactions to guest molecules ,,, , that can also form free-radical intermediates, important to hydrogenation reactions in general , and for benzene in particular. ,,,, Other than from muon science ,,, though, exemplified by the present paper as well, there are very few examples of the direct observation of such H-adduct free radicals by spectroscopic techniques, notable exceptions relevant here being the HĊ 6 H 6 cyclohexadienyl radical seen in ZSM-5 zeolite and the ethyl CH 3 ĊH 2 and HĊ 6 H 6 radicals interacting with PdNPs investigated by ESR in silica environments . While ESR would generally be the technique of choice for the investigation of free radicals, the confined geometries of mesoporous silica environments can facilitate radical–radical recombination reactions, reducing signal amplitudes which are generally quite weak to begin with, particularly at higher temperatures, as well as likely affecting the measurements of reaction rates in such confined environments …”
Section: Introductionmentioning
confidence: 75%